Educação matemática : processo de resolução de problemas no contexto escolar - Hübner, Magda Cristina Santin (2010)
The current study had the objective of investigating the pedagogical practice itself as a mathematics teacher, analyzing the mathematical problems solving process within the modality of interactions which happened in real situations in the classroom to identify possible didactic variable to enhance learning. The subjects of the study were 26 students from the sixth grade of elementary school from a private school in Erechim/RS. This research is a qualitative approach associated to the autoscopy procedure which has a study material collected from September to November/2009 through video and audio recordings, math teacher s memories, the class reports and the lesson plans and the student s written production registered in the problems solving activities. Among these problems, five of them were selected and originated the five episodes which were analyzed. The collected information was organized in episodes that were structured in dialogue sequences using the relevance of heuristic math problems solving and peculiarities of the resolution process. The analysis verifies that when the proposed problem solving activities evoke at students characteristics of a true math problem, they promote learning. The same happens related to the use of heuristic problem solving and the peculiarities of the resolution process associated to the interventions of the teacher, the pair interactions and the methodological aspects of teaching.All of them were recognized as didactic variable to encourage and enhance learning. From the analysis, it was possible to think about the importance of effective participation in the classroom interaction, the dialogue between subjects, the diversity of resolution forms, the connection of math knowledge, the variation of kinds of problems and also the importance of the math teacher reviewing the didactic background of their teaching